Pelaksanaan Peradilan In Absentia dalam Penanganan Tindak Pidana Korupsi dikaitkan dengan Hak Asasi Manusia (HAM) - Sayyid Umar Al Masyhur; Tjokorda Istri Kumari Maharatu Pemayun; Luh Putu Rahayu Gita Pertiwi; Komang Giri Arta (Perspektif Hukum, 2020)
Justice in absentia In the criminal act of corruption has been the pros and cons to date, there is an assumption that the trial in absentia is a violation of human rights because it is related to the human rights of the accused as a human being who has the right to defend himself in court, on the other hand the trial in absentia can be carried out as long as the defendant is completely unknown so that he cannot be present at the trial hearing due to running away (fugitive). This paper discusses the implementation of justice in absentia in the handling of criminal acts of corruption associated with human rights in efforts to save state finances, this study aims to determine whether the trial process of a court hearing a defendant can be sentenced to a criminal sentence by a judge without the defendant himself being present. a judicial process in absentia. The research method used is normative research using data collection methods, namely library research (library research) by searching, reading and studying and understanding secondary data related to the problem under study. The results of this study indicate that trials in absentia can be implemented and do not violate human rights as long as they are implemented through correct procedures and based on statutory provisions. The in absentia trial aims to break the impasse in examining defendants who are not present at the trial and efforts to save state finances, both those that have been corrupted and those that are still suspected of having something to do with corruption cases, both those that have been confiscated and those that have not been confiscated to be confiscated for the state through a court decision.